Circulating circRNA: a social butterfly in tumors - Miao, Shuo; Zhang, Qingsong (Frontiers in Oncology, 2023)
Circular RNAs (circRNAs) are a class of single-stranded non-coding RNAs that form circular structures through irregular splicing or post-splicing events. CircRNAs are abnormally expressed in many cancers and regulate the occurrence and development of tumors. Circulating circRNAs are cell-free circRNAs present in peripheral blood, they are considered promising biomarkers due to their high stability. In recent years, more and more studies have revealed that circulating circRNAs participate in various cellular communication and regulate the occurrence and development of tumors, which involve many pathological processes such as tumorigenesis, tumor-related immunity, tumor angiogenesis, and tumor metastasis. Understanding the role of cell communication mediated by circulating circRNAs in tumor will further reveal the value and significance behind their use as biomarkers and potential therapeutic targets. In this review, we summarize the recent findings and provide an overview of the cell-cell communication mediated by circulating circRNAs, aiming to explore the role and application value of circulating circRNAs in tumors.